Improving the Critical Thinking Ability Science through Problem-Based Learning Model Assisted Student Worksheet Ethnoscience - Dian Armadha Wahyuningtyas; Fauzatul Ma'rufah Rohmanurmeta; Sri Widyastuti (Jurnal PTK dan Pendidikan, 2023)
Abstract: This research was motivated by the results of tests of critical thinking abilities in science in the pre-cycle of fifth-grade students at Kauman 2 Ponorogo Elementary School who were at a low level. Through the initial data, it was found that 80% of the 15 students had a low category critical thinking ability test score. The purpose of this study was to improve critical thinking skills in science through a Problem-Based Learning (PBL) based learning model assisted by the Ponorogo ethnoscience worksheet. The research approach used is Classroom Action Research, which adopts the stages of the Kurt Lewin cycle. The stages used in this research include: planning, action, and reflection. The research implementation lasted for two cycles with two meetings in each cycle. Based on the results of the research that has been carried out, the percentage of students' classical completeness in cycle 1 has increased by 40% to 60%. While in cycle 2 again experienced an increase of 27% to 87%. Therefore, it can be concluded that the implementation of the Problem-Based Learning model assisted by the Ponorogo ethnoscience worksheet can improve the critical thinking ability of science students in fifth grade at the elementary school level.Keywords: Problem-Based Learning, Ethnoscience, Critical Thinking Ability.Abstrak: Penelitian ini dilatarbelakangi oleh hasil tes kemampuan berpikir kritis IPA pada pra-siklus pada peserta didik kelas V SDN 2 Kauman Ponorogo yang berada pada level rendah. Melalui data awal diperoleh hasil bahwa 80% dari 15 peserta didik memiliki nilai tes kemampuan berpikir kritis dengan kategori rendah. Tujuan dari penelitian ini adalah guna meningkatkan kemampuan berpikir kritis IPA melalui model pembelajaran berbasis Problem-Based Learning (PBL) berbantu LKPD etnosains daerah Ponorogo. Pendekatan penelitian yang digunakan yakni PTK (Penelitian Tindakan Kelas) dengan mengadopsi tahapan siklus Kurt Lewin. Adapun tahapan yang digunakan dalam penelitian meliputi: perencanaan, pelaksanaan tindakan, pengamatan, dan refleksi. Pelaksanaan penelitian berlangsung selama dua siklus dengan dua kali pertemuan setiap siklusnya. Berdasarkan hasil penelitian yang telah dilaksanakan, persentase ketuntasan klasikal peserta didik pada siklus 1 mengalami kenaikan sebesar 40% menjadi 60%. Sementara pada siklus 2 kembali mengalami peningkatan sebesar 27% menjadi 87%. Oleh sebab itu dapat disimpulkan bahwa penggunaan model pembelajaran Problem-Based Learning berbantu LKPD etnosains Ponorogo dapat meningkatkan kemampuan berpikir kritis IPA peserta didik kelas V tingkat sekolah dasar.Kata Kunci: Problem-Based Learning, Etnosains, Kemampuan Berpikir Kritis.